N,S co-doped biocarbon for supercapacitor application: Effect of electrolytes concentration and modelling with artificial neural network - Oladipo, Akeem Adeyemi (Elsevier Science Sa, 2021)
Here, nitrogen and sulfur co-doped chicken bone-derived biocarbon (CB0.5-N,S) was prepared using thiourea and K3Fe(CN)(6) as a dopant and graphitization enhancer, respectively. The CB0.5-N,S possesses a suitable graphitization degree (0.87), improved wettable carbon surface, large specific surface area (1615.6 m(2) g(-1)) and wide pore size (2.17 nm) suitable to accommodate fully solvated organic and aqueous electrolyte ions. Typically, CB0.5-N,S delivered a high specific capacitance of 493.9 F g(-1) with excellent capacitance retention of 97.6% and low electrode resistance (R-e) of similar to 0.82 and 0.98 Omega cm(2) before and after 6000 cycling tests, respectively. Also, CB0.5-N,S//CB0.5-N,S symmetric supercapacitor was assembled in an aqueous (1 M H2SO4, 6 M KOH, 1 M Li2SO4) and organic electrolytes (1 M TEABF(4)/acetonitrile); and delivered a high energy-power output. 80.8 W h kg(-1) and 59.7 W h kg(-1) energy densities were delivered at a power density of 2.5 and 1.3 kW kg(-1) in 2 M TEABF4/AN and 1 M H2SO4 at 1 A g(-1), respectively. After 30,000 epoch trains, the developed artificial neural network (ANN) model predicted the performance of the symmetric capacitor with values closely matched to the experimental results at an average desirability function of 0.96 and R-2 of 0.964.
Keywords: Supercapacitor; Energy storage devices; Porous biocarbon; Chicken bone wastes; N; S-Co-doping; Aqueous-organic electrolyte